2022
DOI: 10.3390/jcm11144174
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII Measurement and Substitution in Trauma Patients after Admission to an Intensive Care Unit

Abstract: Trauma patients admitted to an intensive care unit (ICU) may potentially experience a deficiency of coagulation factor thirteen (FXIII). In this retrospective cohort study conducted at a specialized trauma center, ICU patients were studied to determine the dependency of FXIII activity levels on clinical course and substitution with blood and coagulation products. A total of 189 patients with a median injury severity score (ISS) of 25 (16–36, IQR) were included. Abbreviated injury scores for extremities (r = −0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Following supplementation of FXIII (i.e., when patients were in the ICU), RBC transfusion was not significantly different between the groups, suggesting that treatment might have a positive effect in stabilizing the patients’ coagulation status. This finding is in line with observations made by Katzensteiner et al who reported a stongly negative correlation between FXIII levels and the amount of RBCs transfused prior to the first FXIII evaluation [ 17 ]. The observed necessity for an increased transfusion of FC, PC as well as additional supplementation of FXIII in some patients during the ICU stay might be related to prolonged bleeding due to more pronounced coagulopathy and prolonged vasopressor therapy in the FXIII group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Following supplementation of FXIII (i.e., when patients were in the ICU), RBC transfusion was not significantly different between the groups, suggesting that treatment might have a positive effect in stabilizing the patients’ coagulation status. This finding is in line with observations made by Katzensteiner et al who reported a stongly negative correlation between FXIII levels and the amount of RBCs transfused prior to the first FXIII evaluation [ 17 ]. The observed necessity for an increased transfusion of FC, PC as well as additional supplementation of FXIII in some patients during the ICU stay might be related to prolonged bleeding due to more pronounced coagulopathy and prolonged vasopressor therapy in the FXIII group.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, and comparable to other studies, e.g. Katzenstensteiner et al, the decision whether to substitute FXIII exclusively based on clinical judgment and independently from FXIII values [ 17 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“… 168 In a larger retrospective study in trauma patients, low factor XIII levels after hospital admission correlated with an adverse clinical course of patients. 169 Replacement of factor XIII levels with factor XIII concentrate failed to reduce transfusion demands. Further clinical studies are needed to clarify the population, dosing interval, and outcomes if using these agents for uncontrollable bleeding.…”
Section: Strategies For Uncontrollable Microvascular Bleedingmentioning
confidence: 99%